Quality of Life in Women with Hirsutism in Erbil City - Roshna Abdulla Ali; Selwa Elias Yacoub (Advanced Medical Journal)
Background and objectives: Hirsutism being a psychological, social and not merely medical problem may have a negative impact on the quality of life of affected women. This study was done to determine the quality of life of women with hirsutism.